Enhancement of FAME productivity of Scenedesmus obliquus by combining nitrogen deficiency with sufficient phosphorus supply in heterotrophic cultivation. (15th November 2015) - Shen, Xiao-Fei; Liu, Jing-Jing; Chu, Fei-Fei; Lam, Paul K.S.; Zeng, Raymond J.
Graphical abstract: Highlights: Scenedesmus obliquus made good use of assimilated acetate for fatty acid accumulation. FAME productivity during nitrogen starvation increased fourfold. Sufficient phosphorus supply played a positive role in enhancing FAME productivity. The fatty acid yields under nitrogen limitation increased 2–4 fold. Abstract: In this study, Scenedesmus obliquus NIES-2280 was cultivated heterotrophically with acetate as the carbon source. The effects of nitrogen deficiency and different phosphorus supply levels on biodiesel production by S. obliquus were investigated. It was found that S. obliquus could make good use of assimilated acetate for fatty acid accumulation. Fatty acid contents of algae in nitrogen deficiency media increased to 38–48% after 6-day cultivation. Interestingly, the productivity of fatty acid methyl esters (FAMEs) under nitrogen starved conditions increased fourfold than that under nitrogen sufficient conditions. Moreover, FAME productivity could be further enhanced by a sufficient phosphorus supply rather than under P limitation or P deficiency conditions, and the highest FAME productivity was 55.9 mg L −1 d −1 . Furthermore, the conversion yields of acetate to fatty acids (COD based) in nitrogen starvation media (18–28%) were much higher than those in nitrogen sufficient media (∼7%). This study indicates a great potential to combine wastewater treatment with biodiesel production via S. obliquus which can significantly improve biodiesel productivity and COD utilization under nitrogen starvation coupled with sufficient phosphorus supply.